2021
DOI: 10.3390/plants11010103
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of N6-Methyladenosine (m6A) Modification Landscape in Response to Drought Stress in Apple (Malus prunifolia (Willd.) Borkh)

Abstract: Drought stress is a significant environmental factor limiting crop growth worldwide. Malus prunifolia is an important apple species endemic to China and is used for apple cultivars and rootstocks with great drought tolerance. N6-methyladenosine (m6A) is a common epigenetic modification on messenger RNAs (mRNAs) in eukaryotes which is critical for various biological processes. However, there are no reports on m6A methylation in apple response to drought stress. Here, we assessed the m6A landscape of M. prunifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…We speculated that the limitations of sequencing may have caused this undetectable m 6 A modification of these enzymes. Based on our previously published m 6 A-seq datasets (Mao et al, 2021), we found these genes can be modified by m 6 A modification. Therefore, we designed primers based on where m 6 A modification occur in previous results to detect m 6 A levels of these enzymes in MdMTA transgenic plants.…”
Section: Mdmta Plays a Positive Role In Promoting Lignin Deposition A...mentioning
confidence: 90%
“…We speculated that the limitations of sequencing may have caused this undetectable m 6 A modification of these enzymes. Based on our previously published m 6 A-seq datasets (Mao et al, 2021), we found these genes can be modified by m 6 A modification. Therefore, we designed primers based on where m 6 A modification occur in previous results to detect m 6 A levels of these enzymes in MdMTA transgenic plants.…”
Section: Mdmta Plays a Positive Role In Promoting Lignin Deposition A...mentioning
confidence: 90%
“…The reader proteins mainly included ECT2/3/4 and CPSF30 [ 6 , 9 ]. m 6 A has been examined in many species, including Arabidopsis [ 11 ], maize [ 12 ], wheat [ 13 ], oat [ 14 ], rice [ 15 ], sea buckthorn and apple [ 16 , 17 ]. Recently, the function of some m 6 A pathway genes in plants has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the m 6 A-mediated stress responses have been extensively studied in ª 2022 The Authors. Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd., 20, 1447-1455 various crops, including tobacco (Nicotiana tabacum) (Li et al, 2018), rice (Cheng et al, 2021;Shi et al, 2019b;Tian et al, 2021;Zhang et al, 2021a), wheat (Sun et al, 2020;Zhang et al, 2021b), sweet sorghum (Zheng et al, 2021), tomato (Yang et al, 2021), apple (Guo et al, 2021;Mao et al, 2021), and pakchoi (Liu et al, 2020).…”
Section: Regulatory Mechanisms Of M 6 a On Crop Stress Responsesmentioning
confidence: 99%
“…Mutation of m 6 A writers in Arabidopsis induces significant changes in the expression of genes responsive to abiotic and biotic stresses, as revealed by transcriptome analysis (Anderson et al ., 2018 ; Bodi et al ., 2012 ; Hu et al ., 2021a ). Accordingly, the m 6 A‐mediated stress responses have been extensively studied in various crops, including tobacco ( Nicotiana tabacum ) (Li et al ., 2018 ), rice (Cheng et al ., 2021 ; Shi et al ., 2019b ; Tian et al ., 2021 ; Zhang et al ., 2021a ), wheat (Sun et al ., 2020 ; Zhang et al ., 2021b ), sweet sorghum (Zheng et al ., 2021 ), tomato (Yang et al ., 2021 ), apple (Guo et al ., 2021 ; Mao et al ., 2021 ), and pak‐choi (Liu et al ., 2020 ).…”
Section: Regulatory Mechanisms Of M 6 a On Crop St...mentioning
confidence: 99%
See 1 more Smart Citation